MICROALBUMINURIA REDUCTION WITH EARLY PHARMACOTHERAPEUTIC INTERVENTION FOR BLOOD PRESSURE CONTROL IN CASES OF HYPERTENSIVE T2DM SUBJECTS - Dr. Sanjay Sud (Medico Research Chronicles, 2019)
Objective: A prospective randomized observational study to assess the importance of early intervention with pharmacotherapy to control B.P. in T2DM having microalbuminuria, and its reduction in comparison to a delayed initiation for the same.Materials and methods: Patients with T2DM, HTN, and Microalbuminuria, on treatment for Diabetes but drug naïve for HTN were selected and divided into two groups. Group A was advised LSM for B.P. control but no pharmacotherapy. Group B gave the same advice plus Azilsartan 40 mg/day. UACR, B.P., and HbA1c were recorded on every visit. Second visit (3 months) Group A added on Azilsartan 40 mg/day to control the B.P. to target. Group B advised titration of Azilsartan dosage for the same. On the third visit (6 months) all the three parameters were recorded as before.Results: (n=66) completed the study. (A=36 and B=30). The data analysis showed that at the end of 6 months ~33% of the patients in Group A could become non-microalbuminuric in comparison to ~67% of the patients in Group B. Reduction in microalbuminuria could be achieved in ~72% of patients from Group A, whereas ~87% of patients could achieve the same in Group B.Conclusion: From the results of this study, it could be concluded that early initiation of pharmacotherapy in hypertensive T2DM patients to reduce B.P. helped to achieve a significantly beneficial effect on microalbuminuria reduction when compared to delayed initiation for the same even when the glycaemic goals and LSM were targeted with equal aggression in both the groups.